2020
DOI: 10.3389/fimmu.2019.03154
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Roles of Endoplasmic Reticulum Stress in Balancing Immunity and Tolerance in Health and Diseases: Mechanisms and Opportunities

Abstract: The endoplasmic reticulum (ER) is an organelle equipped with mechanisms for proper protein folding, trafficking, and degradation to maintain protein homeostasis in the secretory pathway. As a defense mechanism, perturbation of ER proteostasis by ER stress agents activates a cascade of signaling pathways from the ER to the nucleus known as unfolded protein response (UPR). The primary goal of UPR is to induce transcriptional and translational programs to restore ER homeostasis for cell survival. As such, defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 169 publications
(192 reference statements)
1
62
0
1
Order By: Relevance
“…Moreover, in the frontotemporal dementia disease, the high levels of p-PERK, p-eIF2α and ATF4 were reduced after orally treating transgenic mouse model with GSK2606414 [ 170 ]. Recently, it was found that this compound is a potential therapy of cancer since it inhibits KIT, a type III receptor tyrosine kinase (RTK), known to activate many signal transduction pathways including RAS/ERK (Extracellular Signal-Regulated Kinase), PI3K/AKT or PKB (Phosphoinositide 3-kinase/ Protein kinase B), phospholipase C, JAK/STAT (Janus kinase/signal transducers and activators of transcription), and Src kinase pathways [ 171 ]. However, it has been reported that GSK2606414 may cause side effects related to pancreatic toxicity [ 169 ] maybe due to the extent of UPR inhibition, weight loss and hyperglycemia [ 158 ].…”
Section: Therapeutic Approaches: Chemical Compounds Targeting the mentioning
confidence: 99%
“…Moreover, in the frontotemporal dementia disease, the high levels of p-PERK, p-eIF2α and ATF4 were reduced after orally treating transgenic mouse model with GSK2606414 [ 170 ]. Recently, it was found that this compound is a potential therapy of cancer since it inhibits KIT, a type III receptor tyrosine kinase (RTK), known to activate many signal transduction pathways including RAS/ERK (Extracellular Signal-Regulated Kinase), PI3K/AKT or PKB (Phosphoinositide 3-kinase/ Protein kinase B), phospholipase C, JAK/STAT (Janus kinase/signal transducers and activators of transcription), and Src kinase pathways [ 171 ]. However, it has been reported that GSK2606414 may cause side effects related to pancreatic toxicity [ 169 ] maybe due to the extent of UPR inhibition, weight loss and hyperglycemia [ 158 ].…”
Section: Therapeutic Approaches: Chemical Compounds Targeting the mentioning
confidence: 99%
“…Endoplasmic reticulum (ER) stress can impede the development of antitumor immune responses through reprogramming of several immune cell populations [116,117]. In macrophages, exosomes derived from liver cancer cells undergoing ER stress promoted the secretion of IL-6, MCP-1, IL-10, and TNF-a through STAT3 signaling [118].…”
Section: Macrophagesmentioning
confidence: 99%
“…Myeloid-derived suppressor cells (MDSCs) are characterized by the accumulation of misfolded proteins in the endoplasmic reticulum (ER), which induces the unfolded protein response (UPR) 140 , 141 . The UPR features an orchestrated upregulation of activating transcription factor 6 (ATF6), inositol requiring enzyme 1 (IRE1α) and PKR-like endoplasmic reticulum kinase (PERK).…”
mentioning
confidence: 99%